Pengaruh Pendekatan Konseling Berbasis Budaya Terhadap Masalah Kesehatan Mental pada Komunitas Adat - Irni Suandari; Kyai Maulana Z.M; Dudy Imanuddin (Assertive: Islamic Counseling Journal, 2025)
Mental health is an important aspect of human life that is often neglected, especially in communities that are still steeped in culture and tradition, such as in Kampung Naga, Tasikmalaya. Kampung Naga is known as a community that upholds local traditional and cultural values, which have a big influence on their perspective on mental health. This research aims to find out culture-based counseling, to find out mental health problems in the traditional community in Kampung Naga Tasikmalaya and to find out the effect of culture- based counseling on mental health problems in the traditional community in Kampung Naga Tasikmalaya. The method used in this research is a descriptive method using a quantitative approach, namely research that attempts to reveal the current situation/conditions by considering past conditions through processing figures obtained from research. The results of the analysis of variable The results of the analysis of variable Y show that the value of mental health problems in the traditional community in Kampung Naga Tasikmalayase is 46.5 which is in the interval between 42.64 – 47.96 with a fair classification. The correlation coefficient between variables X and Y is 0.74. The sperm rank correlation figure is on the Guildford scale interval 0.61-0.80 with high qualifications. This means that there is a high influence between culture-based counseling on mental health. Through hypothesis testing it is known that the correlation figure is significant, because it is proven that the t_count of 6.89 is greater than the t_table of 1.686. Thus it is concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Keywords: Culture-based Counseling, Mental Health, Indigenous Community